IMPLEMENTASI PROGRAM ELECTRONIC TRAFFIC LAW ENFORCEMENT DI SATUAN LALU LINTAS POLRESTABES KOTA SEMARANG - Anaya Tahiyyah Salsabila; Aufarul Marom; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2023)
In the current era of globalization, there is a current of globalization which gives changes to the development of information, communication and technology that have an impact on aspects of life. Advances in technology can improve quality public services based on technology and information and communication. The Indonesian National Police is one of the organizations that applies technology to improve its services with Electronic Traffic Law Enforcement (ETLE) or electronic ticketing services in the Traffic Directorate. This study aims to find out how the implementation of Electronic Traffic Law Enforcement in Semarang City and see what are the inhibiting factors and supporting factors in the implementation of Electronic Traffic Law Enforcement. Data collection used observation techniques and interviews with the Semarang City Police Traffic Unit Head, Members of the Semarang City Police Traffic Unit, and the public who are the targets of the Electronic Traffic Law Enforcement program. This study uses data reduction analysis, data presentation, and conclusions. The results of this study show that there are still deficiencies in the implementation of the Electronic Traffic Law Enforcement program in the city of Semarang, such as the lack of direct socialization with the community and the frequent occurrence of errors in ETLE's back office systems. Suggestions from the author are that the Semarang City Police Traffic Unit can socialize with motorized vehicle users when making a driving license (SIM). And making billboards on the streets full of drivers in the city of Semarang for the ETLE program and also the SOP regarding this ETLE. As well as the need for an additional number of ETLE cameras.